Antibacterial potential of marine fungus Aspergillus nomius isolated from green algae Bornetella sp - Sumilat, Deiske Adeliene; Lintang, Rosita A. J. (Sam Ratulangi University, 2021)
Isolation of marine fungi symbiont of green algae Bornetella sp as a producer of antibacterial compounds has been carried out. This study aims to obtain symbiont fungi from green algae Bornetella sp which produces antibacterial compounds. The symbiont fungus was isolated using the direct planting method. Screening for the antibacterial activity of pure symbiont fungi isolates against Escheriscia coli and Staphylococcus aureus, and was carried out by the agar diffusion method. The isolation results obtained 4 isolates, but the one with the most potential to inhibit the growth of the tested bacteria was MFALM2. Molecular characterization showed that the MFALM2 isolate was identified as Aspergillus nomius with a 100% closeness level. Keywords: isolation; marine fungi; Aspergillus nomius; green alga; Bornetella sp.Â AbstrakIsolasi jamur laut yang bersimbion dengan alga hijau Bornetella sp sebagai penghasil senyawa antibakteri telah dilakukan. Penelitian ini bertujuan untuk memperoleh jamur simbion dari alga hijau Bornetella sp yang menghasilkan senyawa antibakteri. Isolasi jamur simbion dilakukan dengan metode direct planting. Skrining aktivitas antibakteri isolat murni jamur simbion terhadap bakteri uji Escheriscia coli dan Staphylococcus aureus dilakukan dengan metode difusi agar.Â Hasil isolasi diperoleh 4 isolat, namun yang paling berpotensi menghambat pertumbuhan bakteri uji adalah MFALM2. Karakterisasi molekuler menunjukkan bahwa isolat MFALM2 teridentifikasi sebagai Aspergillus nomius dengan tingkat keeratan sebesar 100%.Kata kunci: isolasi; jamur lau; Aspergillus nomius; alga hijau; Bornetella sp.